2021
DOI: 10.1111/pops.12775
|View full text |Cite
|
Sign up to set email alerts
|

The Political Psychology of COVID‐19

Abstract: The COVID‐19 pandemic has given rise to unprecedented and extraordinary conditions. It represents a profound threat to health and political and economic stability globally. It is the pressing issue of the current historical moment and is likely to have far‐reaching social and political implications over the next decade. Political psychology can inform our preparedness for the next phase of the pandemic as well as our planning for a post COVID‐19 world. We hope that this special issue will play its part in help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 41 publications
2
31
0
1
Order By: Relevance
“…This result reflects both the widespread impact of the Covid-19 pandemic and the inclusion of Covid experiences by family and friends. This is consistent with the emerging literature on the Covid-19 pandemic ( Muldoon et al, 2021 ; Ruisch et al, 2021 ) but in contrast with Aviña and Sevi's (2021) findings that knowing people diagnosed or to have died from COVID increased the likelihood of voting for Biden.…”
Section: Discussionsupporting
confidence: 89%
“…This result reflects both the widespread impact of the Covid-19 pandemic and the inclusion of Covid experiences by family and friends. This is consistent with the emerging literature on the Covid-19 pandemic ( Muldoon et al, 2021 ; Ruisch et al, 2021 ) but in contrast with Aviña and Sevi's (2021) findings that knowing people diagnosed or to have died from COVID increased the likelihood of voting for Biden.…”
Section: Discussionsupporting
confidence: 89%
“…Societies can only function if people look out for each other as well as themselves. Indeed research has found that a sense of shared identity and community has been shown to be crucial to adherence, mutual aid, and wellbeing during the pandemic 17. In stressing the personal to the exclusion of the social, the government is promoting a fractured, selfish culture that is to the detriment of everyone.…”
mentioning
confidence: 99%
“…Since the beginning of 2020, the world has been facing a pandemic of the new SARS-CoV-2 virus. To contain the spread of the virus, political measures were taken that, under normal circumstances, would be classified as authoritarian, such as closing borders and stores or restricting personal freedoms (Muldoon et al, 2021). State leaders were confronted with the difficult task of explaining the measures to the population, contributing to meaning-making, and strengthening social cohesion (Montiel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%